PENGARUH LATAR BUDAYA TERHADAP PENGGUNAAN BAHASA DALAM ANTOLOGI CERPEN KOLECER DAN HARI RAYA HANTU - Merry DEbby Aritonang (LOA: Jurnal Ketatabahasaan dan Kesusastraan, 2017)
It was interesting to study literary works containing local language vocabulary because it showed its community life. The goal of this study was to describe the influence of cultural background on the use of languages in short stories of Antara Bali and Balige by Cesillia Ces, Pastu karya Oka Rusmini, Baminantu by Sastri Yunizarti Bakry, dan Lali Panggora by Saut Poltak Tambunan. This research used sociolinguistic approach. The researcher collected the data by documenting the local language in Antara Bali and Balige by Cesillia Ces, Pastu karya Oka Rusmini, Baminantu by Sastri Yunizarti Bakry, dan Lali Panggora by Saut Poltak Tambunan. The data collection had a correlation with the social cultural concept in the stories. It revealed that cultural backgrounds influenced the use of language, such as vocabulary and terms of address.